AVAILABILITY OF SEEDS OF SILLAGO SIHAMA FOR FARMING ALONG SOUTH KANARA COAST - Ramamurthy, S; Dhulkhed, M H (Indian Journal of Fisheries, 2011)
The availability of seeds of the Indian Sand Whiting (Sillago sihama) andthe prospects of mariculture of this species on the edge of the South Kanara coasthave been pointed out